(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. Prologo - 2. A mo’ d’introduzione - 3. Storia delle origini od origini di una storia? - 4. Fra’ tacere’ e ’dire’, fra ’ordinare’ e ’interdire’ ... - 5. Rottura di un equilibrio - 6. Emanciparsi dalla Sharîʻa o applicarla? La disputa fra Corano e Sunna - 7. Solo il Corano basta - 8. La critica degli orientalisti - 9. Ulteriori studi: ICMA (isnad-cum-matn analysis)- 10. Maqâsid al-Sharîʻa (le finalità della legge islamica) - 11. Stimoli e riflessioni da un tentativo di approccio comparativo - 12. Una possibile ‘inversione’ di tendenza? - 13. Con il tempo e con la paglia … Quran and/or Sunna? Narrative and prescriptive function in the ’sources’ of Islam ABSTRACT: Even if in different forms and according to historical and anthropological factors that have conditioned their development, religions have a doctrinal part and precepts that can have different weight and priorities in each of them. Islam, which like Judaism is centered more on orthopraxis than on orthodoxy, over time and especially in the modern era, also in relation to the phenomenon of huge migrations of its faithful to the West, is faced with new challenges affecting its regulatory side. In this regard, various orientations and studies have long confronted each other and still animate a little-known debate outside the circle of specialists.